Kelayakan Penataan Lokasi Strategis PKL pada Ruang Terbuka Hijau (RTH) Taman Bungkul Surabaya - Sulistyono, Damar; Wisesa, Dheva Nafis Ardhan; Budi, Gian Mahardika Setia (REKSABUMI, 2025)
Green Open Space (GOS) plays an important role in the sustainability of urban environments. Bungkul Park, Surabaya, as one of the GOS icons, faces challenges from informal economic activities, especially street vendors (PKL). This study aims to analyze the strategy for arranging street vendors in Bungkul Park with a focus on the balance of ecological, aesthetic, and social functions of GOS. Qualitative descriptive methods are used to evaluate the distribution patterns of street vendors, location selection factors, and implementation of local policies. The results show that the success of the arrangement depends on location accessibility, visibility, and stakeholder involvement. Optimal arrangement requires an integrated approach between policy and community needs.